DEVONIAN PALEOGEOGRAPHY AND SEDIMENTATION SETTINGS IN THE SOUTH SIBERIAN PLATFORM - Akulov N.I. (My University, 2004)
The Early Paleozoic regression resulted in emergence of the Angaraland. Devonian deposits accumulated in various sedimentary basins, e.g., in gulfs far incised into the Angaraland, as well as in lagoons and lakes. In marginal areas of the platform, the Rybnaya and Pribaikal'skii sedimentary basins in the foredeep accumulated the molasse sequences during their early evolutionary stages. In the Angaraland, there were plains and uplands of different kinds, which experienced denudation. Erosion of these landforms affected various formations, the diamond-bearing kimberlite bodies included.
Keywords: Devonian; Paleozoic::Devonian; Палеозой::Девонская